Cavernous Hemangioma of the Bladder - Mahdavi, Reza; Rahmani, M (Urology Journal, 2009)
Bladder cavernous hemangioma (BCH) is a rare cause of hematuria. It may appear in every part of the urinary tract and presents mostly in childhood. Bladder hemangioma (BH) is suspected by cystoscopy and radiologic findings and confirmed by pathologic examinations. The treatment of BH differs from partial cystectomy and endoscopic removal or LASER therapy. Since BCH is a rare case and because of its big size and specific cystoscopic findings, we report a treated case of it in this article.